2012
DOI: 10.1111/j.1600-0404.2012.01697.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of moderate-to-severe traumatic brain injuries after reduction in alcohol prices

Abstract: The reduction in alcohol prices and the concomitant increase in alcohol consumption did not increase the incidence of alcohol-related moderate-to-severe TBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 24 publications
1
16
1
Order By: Relevance
“…The age span and the TBI severity may limit generalization of the results. However, the demographic and injury characteristics were similar to other studies on moderate-to-severe TBI (10,36). As the level of consciousness in the early phase of TBI might be obscured because of substance influence, medical sedation, seizures, shock, etc., we cannot rule out a potential bias introduced by using early GCS score as the inclusion criteria (1).…”
Section: Pcs Mcssupporting
confidence: 69%
“…The age span and the TBI severity may limit generalization of the results. However, the demographic and injury characteristics were similar to other studies on moderate-to-severe TBI (10,36). As the level of consciousness in the early phase of TBI might be obscured because of substance influence, medical sedation, seizures, shock, etc., we cannot rule out a potential bias introduced by using early GCS score as the inclusion criteria (1).…”
Section: Pcs Mcssupporting
confidence: 69%
“…Nevertheless, it is known that alcohol related falls are often associated with severe craniofacial trauma and alcohol intoxication is also a well known risk factor for TBI . Moreover, alcohol and older age predicts fatal outcome . The mortality (defined as GOS 1) in our study was 18.2% but Brazinova et al report a wide range of mortality rates in their systematic review on TBI in Europe; from 9/100.000/year to 28/100.000/year in national level studies like ours, but those numbers include all TBI, not only TBI admitted to the ICU .…”
Section: Discussioncontrasting
confidence: 56%
“…). A borderline significant link was found when we omitted Gururaj's () study (OR = 0.90, 95% CI = 0.82 to 0.99), Puljula and colleagues () study (OR = 0.90, 95% CI = 0.82 to 0.99), Pandit and colleagues () (OR = 0.90, 95% CI = 0.82 to 0.99), or Lin and colleagues () study (OR = 0.89, 95% CI = 0.81 to 0.97). The other results of sensitivity analysis for different BACs were not altered.…”
Section: Resultsmentioning
confidence: 83%
“…Our initial result found that alcohol exposure at the time of injury did not decrease the mortality rate, which is not consistent with the 2 previous meta‐analyses. Despite the potential neuroprotective mechanisms, numerous recently published studies also confirmed that alcohol exposure did not decrease or increase mortality rate (Lin et al., ; Pandit et al., ; Puljula et al., ). Nevertheless, the notable heterogeneity and the results of sensitivity analysis of our current results leave the conclusion ambiguous.…”
Section: Discussionmentioning
confidence: 94%